Uptake and provision of self-care interventions for sexual and reproductive health: findings from a global values and preferences survey - Logie, Carmen H.; Berry, Isha; Ferguson, Laura; Malama, Kalonde; Donkers, Holly; Narasimhan, Manjulaa (Sexual and Reproductive Health Matters, 2022)
Self-care interventions hold the potential to improve sexual and reproductive health (SRH) and well-being. Yet key knowledge gaps remain regarding how knowledge and uptake vary across different types of self-care interventions. There is also limited understanding of health workers' confidence in promoting SRH self-care interventions, and how this may differ based on personal uptake experiences. To address these knowledge gaps, we conducted a web-based cross-sectional survey among health workers and laypersons from July to November 2018. We investigated the following information about SRH self-care interventions: knowledge and uptake; decisions for use; and associations between health workers' uptake and providing prescriptions, referrals, and/or information for these interventions. Participants (n = 837) included laypersons (n = 477) and health workers (n = 360) from 112 countries, with most representation from the WHO European Region (29.2%), followed by the Americas (28.4%) and African (23.2%) Regions. We found great heterogeneity in knowledge and uptake by type of SRH self-care intervention. Some interventions, such as oral contraception, were widely known in comparison with interventions such as STI self-sampling. Across interventions, participants perceived benefits of privacy, convenience, and accessibility. While pharmacies and doctors were preferred access points, this varied by type of self-care intervention. Health workers with knowledge of the self-care intervention, and who had themselves used the self-care intervention, were significantly more likely to feel confident in, and to have provided information or referrals to, the same intervention. This finding signals that health workers can be better engaged in learning about self-care SRH interventions and thereby become resources for expanding access.